2014
DOI: 10.1111/apt.13034
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral therapy improves post‐hepatectomy survival in patients with hepatitis B virus‐related hepatocellular carcinoma: a prospective‐retrospective study

Abstract: SUMMARY BackgroundThe effect of antiviral therapy on the post-hepatectomy long-term survival in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 43 publications
1
51
2
Order By: Relevance
“…Chong et al treated patients who underwent hepatectomy for HBV-related HCC with oral NAs treatment, including entecavir and lamivudine, and observed that antiviral therapy was associated with better liver function reserve at the time of recurrence. Furthermore, a greater proportion of these patients were able to receive curative treatment for cancer recurrence [29]. This study also suggests that the timing of antiviral therapy (before or after operation) does not make a distinct difference between the hazard ratios.…”
Section: Antiviral Treatment In Hepatectomymentioning
confidence: 64%
“…Chong et al treated patients who underwent hepatectomy for HBV-related HCC with oral NAs treatment, including entecavir and lamivudine, and observed that antiviral therapy was associated with better liver function reserve at the time of recurrence. Furthermore, a greater proportion of these patients were able to receive curative treatment for cancer recurrence [29]. This study also suggests that the timing of antiviral therapy (before or after operation) does not make a distinct difference between the hazard ratios.…”
Section: Antiviral Treatment In Hepatectomymentioning
confidence: 64%
“…In patients who have developed HCC, improvements in surgical, locoregional and systemic therapies further contribute to better survival [6]. In addition, antiviral therapy after liver resection may reduce HCC recurrence and mortality [7][8][9].…”
Section: Chronic Hepatitis B Virus (Hbv) Infection Affects Over 350 Mmentioning
confidence: 99%
“…The etiology of HCC and the severity of cirrhosis are also associated with overall survival in HCC patients [1517]. The use of postoperative antiviral therapies for viral hepatitis B (HBV)- and hepatitis C (HCV)-related HCC reportedly reduce HCC recurrence and enhance overall survival [1820]. Different combinations of genes associated with cell proliferation and the tumor microenvironment are also employed as genomic prognostic markers for HCC [21, 22].…”
Section: Introductionmentioning
confidence: 99%